Penggunaan Robotik bagi Projek Pembinaan Infrastruktur di Malaysia - Nik Aizul Eddie Ezral; OMAR, ROSHARTINI; Sarpin, Norliana; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2025)
Robotics has become one of the technologies increasingly utilized in the construction industry today, particularly for infrastructure projects. However, alongside its adoption, the use of this technology also presents challenges for the construction industry. The acquisition of such technology inevitably incurs significant costs. Therefore, the objective of this study is to examine the potential of robotics technology in infrastructure projects, the constraints faced in its use, and strategies to enhance its adoption in Malaysia’s construction industry. The target respondents for this study are construction site workers, including contractors, engineers, site supervisors, and skilled laborers familiar with the use of this technology. The research employs a quantitative method to gather data and distributes questionnaires through Google Forms to the respondents. Data collected were analyzed descriptively using the Statistical Package for the Social Sciences (SPSS) software version 26, released in 2019. The population and sample size of respondents were determined based on the Krejcie and Morgan Table (1970). A population of 170 was used, with a sample size of 118 respondents, equivalent to a 100% response rate. The study focuses on Kuala Lumpur, where several companies already use robotics technology. The questions posed to respondents align with the study’s objectives, namely to assess the potential of robotics technology, the challenges faced, and strategies to enhance its use in infrastructure projects in Malaysia. The findings demonstrate that the potential use of robotics related to improving safety was strongly supported by the majority of respondents (92%). Meanwhile, the primary constraint faced was worker resistance to the technology, with 87.3% of respondents agreeing. Lastly, the data indicates that the most effective strategy involves government initiatives regarding robotics technology, with 90.2% of respondents in agreement. This study is therefore important in raising public awareness of robotics technology, which can make a significant contribution to Malaysia’s construction industry.